Comparison of the effects of cefazolin and ceftriaxone on canine chondrocyte culture - Siengdee P. (2017)
Cephalosporins (CEFs) are antibiotics frequently used to treat bone infections and septic arthritis. The effects of CEFs on chondrocytes have not been studied until now. Cefazolin (cef1) and ceftriaxone (cef3), first-and third-generation CEFs, were selected to investigate their direct effects on normal and osteoarthritic (OA) primary canine chondrocytes, which were either nonstimulated or stimulated with the pro-inflammatory cytokine IL-1β. In our results, treatment with CEFs increased the negative effects on both conditioned normal and OA chondrocytes, especially when applied to IL-1β-stimulated cells (inflammatory stimulus). CEFs significantly decreased cell viability and induced apoptotic cell death in both normal and OA chondrocytes; moreover, treatment with cef1 caused necrotic cell death in OA chondrocytes. Cef3 treatment could increase s-GAG synthesis in normal cells preincubated with IL-1β, while cef1 had no significant effect. The expression of TNF was clearly downregulated after cef3 treatments, whereas it was upregulated after cef1 treatments. However, cef3 induced stronger downregulation of TIMP1 and the extracellular matrix component genes COL2A1 and ACAN. In conclusion, these results suggest both the cytotoxic effects of CEFs and their adverse effects on chondrogenic marker genes at the transcriptional level, which provide additional insight into the clinical application of cef1 and cef3. 2017 John Wiley & Sons Ltd.